Yield Criterion of the Softwood under Conditions of Variable Humidity - Kowal, M.; Mielniczuk, J. (Engineering Transactions, 2015)
Wood is a porous material. In a dry state the unit volume of wood consists of water-free volume of the wood substance, the so-called wood skeleton, and of the air-filled pores. The variable humidity produces the internal forces within the loaded wood bulk loading to destruction in the form of loosening wood fibers, cracks and twists. In the paper the yield criterion or the transition of the softwood into the plastic state is discussed. The outset of yielding is examined in accordance with the Hill criterion for anisotropy with various ratios of humidity. The case of plane stress with the orthotropic structure is used as an example for which the material constants are identified, resulting in a special form of the yield criterion.